Relationship marketing: theorethical aspects - Juščius, Vytautas; Navickas, Valentinas; Jonikas, Donatas (Business: Theory and Practice, 2006)
In recent years relationship marketing has found its place in the practice of modern production and service busi- ness. In Lithuania this concept is yet in the first stages of its development. The article focuses on the concept of relationship marketing and its development within the context of various marketing theories. The main principles of application and methods of relationship marketing are analyzed. The key assumptions for using relationship marketing as well as factors of influence are disclosed. The article also examines the specifics of relationship marketing in the service sector, evaluates opportunities for adapting well-known forms and methods of relationship marketing in this field. The authors conclude that maintaining relationships and partnerships between countries helps in formulating company competency and competitive advantages. Actively used relationship marketing increases the value of a company’s offerings in the modern market. Based on the finding of recent empirical research the authors claim that relationship marketing for service sector firms is a way of formulating competitive advantages that are important and difficult to replicate. Article in Lithuanian. Santykių marketingas: teoriniai aspektai Santrauka. Pastaraisiais metais santykių marketingas jau yra įsitvirtinęs modernioje gamybinio ir paslaugų verslo praktikoje. Lietuvoje ši verslo koncepcija dar tebėra pradinės raidos stadijos. Straipsnyje nagrinėjama santykių marketingo samprata ir jos evoliucija įvairių marketingo teorijų kontekste. Analizuojami pagrindiniai santykių marketingo taikymo principai ir metodai. Atskleidžiamos esminės marketingo santykių taikymo prielaidos ir įtakos veiksniai. Tyrinėjama santykių marketingo specifika paslaugų rinkoje, vertinamos paplitusių santykių marketingo metodų ir formų adaptavimo galimybės šioje sferoje. Daroma išvada, kad santykių palaikymas ir šalių partnerystė padeda formuoti įmonės kompetenciją ir konkurencinį pranašumą. Remiantis pastarųjų metų empiriniais tyrimais teigiama, kad santykių marketingas paslaugų įmonėse tampa itin svarbiu sunkiai nukopijuojamu konkurencinių pranašumų formavimo būdu. Reikšminiai žodžiai: santykių marketingas, klientų pritraukimas, ryšių palaikymas ir stiprinimas, vartotojų lojalumas.